Differences in the effects of Kenyan, Tanzanian, and Ethiopian coffee intake on interstitial glucose levels measured by FreeStyle Libre: A pilot case study - Junichi Okada, MD, PhD; Aya Osaki, MD, PhD; Yoko Shimoda, MD, PhD; Eijiro Yamada, MD, PhD; Tsugumichi Saito, MD, PhD; Atsushi Ozawa, MD, PhD; Yasuyo Nakajima, MD, PhD; Kazuya Okada, MD; Shuichi Okada, MD, PhD; Masanobu Yamada, MD, PhD (Elsevier, 2020)
ABSTRACT: Background: Although generally considered part of a healthy diet, coffee consumption has been suspected to be associated with elevated epinephrine levels and increasing insulin resistance. Objectives: We studied the effects of the intake of 3 different types of coffee (Tanzanian, Ethiopian, and Kenyan) on postprandial interstitial glucose levels. Method: Interstitial glucose levels were measured every 15 minutes using the FreeStyle Libre glucose monitoring system (Abbott Diabetes Care Ltd, Witney, United Kingdom) in each individual after drinking coffee compared with when not consuming coffee. Results: Unlike Tanzanian and Ethiopian coffees, Kenyan coffee suppressed the increase of postprandial interstitial glucose levels. Kenyan coffee beans contain less anhydrous caffeine and more chlorogenic acid than Tanzanian and Ethiopian coffee beans. These findings may explain the different effects of these coffee types on postprandial interstitial glucose levels. Furthermore, Kenyan coffee beans inhibited α-glucosidase activity, which may partially explain why Kenyan coffee reduces postprandial interstitial glucose levels. Conclusions: Coffee is widely consumed as a beverage worldwide, and our findings suggest that patients with diabetes mellitus may benefit from drinking Kenyan coffee because of its ability to reduce postprandial interstitial glucose levels. (Curr Ther Res Clin Exp. 2020; 81:XXX-XXX)